Pengaruh Disiplin Kerja dan Motivasi Terhadap Kinerja Karyawan di PT. Suryabumi Agrolanggeng - Vika Lidya Sari; Muhammad Ichsan Hadjri; Wita Farla (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of work discipline and motivation on employee performance at PT Suryabumi Agrolanggeng. This study uses a quantitative method with census techniques, where the entire population consisting of 132 employees of the Palm Oil Mill is used as respondents. The instrument used was in the form of a questionnaire, and the data were analyzed by multiple linear regression tests. The results of the study show that simultaneously or partially, work discipline and motivation have a positive and significant effect on employee performance. Based on these results, it can be concluded that the higher the discipline and motivation of employees, the better the performance will be.